LEARNING DIFFICULTIES: ETIOLOGY, PREDISPOSING FACTORS AND INTERVENTION STRATEGIES - Abekhale, Samson Olorunda; Egbe-Okpenge, Grace Enochojo (Sokoto Educational Review, 2020)
The dearth of relevant information about issues regarding learning difficulties in relation to the School-age children in Nigeria, formed the basis of this paper. The fact that the concept of learning difficulty is relatively new, is not an indication that it has not been in existence. Learning difficulties could be seen to be as old as learning itself. The much emphasis on physical impairments such as mental retardation, blindness, deafness, impulsivity and hyperactivity overshadowed the attention that should have been given to learning difficulties. But with the overwhelming global increase in educational problems in the 20th and 21s' centuries, it has become obvious that the main issues affecting learning be given due consideration. This paper therefore established a position that learning difficulties which have affected over 2.9 million school-age children in the United States of America, exist also in Nigeria in apparently greater dimension. It is a heterogeneous disorder, which poses difficulty in reading, writing and mathematical calculations. This paper observes that the disorder is capable of devastating the social, psychological and educational well-being of an individual. Though a lifelong problem which ranges from mild to severe, its actual causation is yet to be determined. This paper has however identified the types of learning difficulties - Dyslexia, Dyscalculia, Dysgraphia, Dyspraxia, Visual and Auditory perceptual deficits and presented the internal and external factors that could predispose learning difficulties. In view of the anticipated negative impacts it may have on School-age children, this paper recommended some intervention or coping strategies that can assist the affected children achieve their educational goals and live successful lives.